The Matter at Hand: A Practice-Theoretical Model of Digital Gaming - Jaćević, Milan (Replay. The Polish Journal of Game Studies, 2019)
Investigations into the nature of the activity of gaming have been made difficult by virtue of the plurality of possible forms this activity may take. In this paper, I address this problem by examining (digital) gaming under the heading of practice theory, in an attempt to shed more light on the practical aspects of ludic literacy. Building on the theoretical and conceptual frameworks of Pierre Bourdieu, I present a general model of digital gaming as a form of situated human practice, followed by details of a case study, conducted in order to test and adjust the initial version of the model. Though further research with a greater population of players is needed in order to expand the scope of the model, the findings of the study lend credence to its validity as a conceptual framework for delineating and framing different practices generated by digital game artefacts.